Positive active slurry as well as preparation method and application thereof

By adding components such as catechol to the positive electrode active slurry of the secondary battery and adopting specific mixing and processing methods, the uniform distribution of conductive agents is solved, and the battery resistance growth and capacity attenuation caused by uneven distribution of conductive agents is achieved, and more stable battery performance and longer equipment service life are achieved.

CN119812239APending Publication Date: 2025-04-11NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411723355.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The uneven distribution of conductive agents in the electrode materials in the secondary battery leads to rapid growth of battery resistance and severe capacity attenuation.

Method used

A positive electrode active slurry is used, which includes a positive electrode active material, a conductive agent, a binder, a catechol and a solvent, and through specific mixing and processing methods, the uniform distribution of the conductive agent is ensured. This slurry is used to prepare a positive electrode sheet, and the uniform distribution of the conductive agent is verified by quality control methods of overdischarge and partitioning the secondary battery.

Benefits of technology

It effectively reduces the resistance growth rate of the battery, improves the cycle stability performance and capacity retention rate of the battery, and thus extends the service life of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812239A_ABST
    Figure CN119812239A_ABST
Patent Text Reader

Abstract

The invention provides positive active slurry as well as a preparation method and application thereof. The positive active slurry comprises a positive active material, a conductive agent, a binder, catechol and a solvent, manufacturing the positive active slurry into a secondary battery, wherein a negative current collector in the secondary battery comprises copper; the secondary battery is overdischarged, the diaphragm in the overdischarged secondary battery is equally divided into n regions, the mass ratio of the copper element in each region on the surface of the diaphragm meets the condition that 1-{[(x1-x) 2 + (x2-x) 2 +... + (xn-x) 2] / (n-1)} 1 / 2 is greater than or equal to 90%, x1, x2,... xn are the mass ratios of the copper element in the first region, the second region,..., and the nth region respectively, x is the average value of the mass ratios of the copper elements in the n regions. The conductive agent in the positive active slurry is uniformly distributed, so that the resistance growth rate of the battery can be effectively reduced, and the cycle stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of secondary batteries and relates to a positive electrode active slurry, in particular to a positive electrode active slurry and a preparation method and application thereof. Background Art

[0002] The large-scale development and use of fossil fuels has led to global warming and serious environmental pollution, which has promoted the development and application of secondary battery technology to reduce dependence on fossil fuels. The biggest advantage of secondary batteries is that they can be charged and discharged repeatedly. Currently, lithium-ion batteries and sodium-ion batteries are widely used.

[0003] As one of the important components of secondary batteries, the positive electrode plays a vital role in the performance of the battery. The conductive agent is an important component of the positive electrode. Its distribution in the electrode material directly affects the electrochemical performance of the battery. The uneven distribution of the conductive agent will affect the wettability of the electrolyte to the electrode, thereby affecting the migration efficiency of lithium ions, resulting in a large increase in resistance during the battery cycle, causing serious battery capacity decay.

[0004] Therefore, it is necessary to improve the distribution uniformity of the conductive agent in the electrode material to reduce the resistance growth of the battery and improve the cycle stability performance of the battery. Summary of the invention

[0005] The present invention provides a positive electrode active slurry, in which the conductive agent is evenly distributed, which can effectively reduce the resistance growth of the battery and improve the cycle stability performance of the battery.

[0006] The present invention provides a quality control method for positive electrode active slurry, by which it can be proved whether the conductive agent in the positive electrode active slurry is evenly distributed, thereby alleviating the problems of excessively fast resistance growth and severe capacity attenuation caused by uneven distribution of the conductive agent.

[0007] The present invention provides a method for preparing a positive electrode active slurry. The conductive agent in the positive electrode active slurry prepared by the method is distributed more evenly, thereby reducing the resistance growth rate and alleviating capacity attenuation.

[0008] The present invention provides a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active layer is prepared from the positive electrode active slurry or the positive electrode active slurry prepared by the preparation method. The positive electrode sheet is used in a secondary battery to effectively alleviate the problem of excessive resistance growth and capacity attenuation caused by uneven distribution of a conductive agent.

[0009] The present invention provides a secondary battery. Since the secondary battery comprises the positive electrode sheet, the secondary battery has a lower resistance growth rate and a higher cycle performance.

[0010] The present invention provides an electronic device, which comprises the secondary battery, so the electronic device has a longer service life.

[0011] The first aspect of the present invention provides a positive electrode active slurry, the positive electrode active slurry comprising a positive electrode active material, a conductive agent, a binder, catechol and a solvent;

[0012] The positive electrode active slurry is made into a positive electrode sheet, and the positive electrode sheet, a separator, and a negative electrode sheet are stacked in sequence to make a secondary battery; wherein the negative electrode sheet includes a negative electrode collector, and the negative electrode collector includes copper;

[0013] The secondary battery is over-discharged, and the area of ​​the separator in the over-discharged secondary battery is divided into n regions, and the mass proportion of the copper element in the first, second, ... nth regions on the surface of the separator satisfies Formula 1,

[0014] 1-{[(x 1 -x) 2 +(x 2 -x) 2 +……+(x n -x) 2 ] / (n-1)} 1 / 2 ≥90% Formula 1

[0015] In formula 1, x 1 、x 2 ,……x n are the mass percentages of the copper element in the 1st, 2nd, ... nth regions respectively, and x is the average mass percentages of the copper element in the n regions.

[0016] The positive electrode active slurry as described above, wherein the mass content of the catechol in the positive electrode active slurry is 0.05-1%;

[0017] And / or, the mass content of the conductive agent in the positive electrode active slurry is 1-10%;

[0018] And / or, the mass content of the binder in the positive electrode active slurry is 1-10%;

[0019] And / or, the mass content of the positive electrode active material in the positive electrode active slurry is 80-98%.

[0020] The positive electrode active slurry as described above, wherein the solid content of the positive electrode active slurry is 48-70%.

[0021] The second aspect of the present invention provides a quality control method for positive electrode active slurry, wherein the positive electrode active slurry of the first aspect is made into a positive electrode sheet, and the positive electrode sheet, a separator, and a negative electrode sheet are stacked in sequence to make a secondary battery; wherein the negative electrode sheet includes a negative electrode current collector, and the negative electrode current collector includes copper;

[0022] The secondary battery is over-discharged, and the area of ​​the separator in the over-discharged secondary battery is divided into n regions, and the mass proportion of the copper element in the first, second, ... nth regions on the surface of the separator satisfies Formula 1,

[0023] 1-{[(x 1 -x) 2 +(x 2 -x) 2 +……+(x n -x) 2 ] / (n-1)} 1 / 2 ≥90% Formula 1

[0024] In formula 1, x 1 、x 2 ,……x n are the mass percentages of the copper element in the 1st, 2nd, ... nth regions respectively, and x is the average mass percentages of the copper element in the n regions.

[0025] The third aspect of the present invention provides a method for preparing the positive electrode active slurry of the first aspect, comprising the following steps:

[0026] Premixing the positive electrode active material, the conductive agent and catechol, wherein the revolution speed is 10-40 rpm, the dispersion speed is 300-600 rpm and the mixing time is 30-60 min to obtain a dry material;

[0027] Mixing the binder with the solvent to obtain a binder glue solution, and dividing the binder glue solution into a first binder glue solution and a second binder glue solution;

[0028] The first binder glue and the dry material are first mixed to obtain a first slurry; in the first mixing, the revolution speed is 20-50 rpm, the dispersion speed is 1000-4000 rpm, the vacuum degree is -40 KPa-85 KPa, and the mixing time is 60-120 min;

[0029] The second binder glue is mixed with the first slurry for a second time to obtain a second slurry; in the second mixing, the revolution speed is 20-50 rpm, the dispersion speed is 1000-4000 rpm, the vacuum degree is -40--100 KPa, and the mixing time is 60-120 min;

[0030] The second slurry is subjected to ultrasonic treatment to obtain a third slurry; the third slurry is subjected to a third mixing with a solvent to obtain the positive electrode active slurry.

[0031] The method for preparing the positive electrode active slurry as described above, wherein the solid content of the binder glue is 3-15%;

[0032] and / or, the weight of the first adhesive glue accounts for 40-60% of the weight of the adhesive glue;

[0033] And / or, the weight of the second adhesive solution accounts for 40-60% of the weight of the adhesive solution.

[0034] The method for preparing the positive electrode active slurry as described above, wherein, in the ultrasonic treatment, the ultrasonic time is 10 to 60 minutes and the vibration frequency is 20 to 100 kHz;

[0035] And / or, in the third mixing, the revolution speed is 20-50 rpm, the dispersion speed is 1000-4000 rpm, the vacuum degree is -40--100 KPa, and the mixing time is 40-120 min.

[0036] A fourth aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector;

[0037] The positive electrode active layer is prepared from the positive electrode active slurry of the first aspect or the positive electrode active slurry prepared by the preparation method of the second aspect.

[0038] A fifth aspect of the present invention provides a secondary battery, comprising the positive electrode sheet according to the fourth aspect.

[0039] A sixth aspect of the present invention provides an electronic device, comprising the secondary battery according to the fifth aspect.

[0040] The positive electrode active slurry in the present invention includes a positive electrode active material, a conductive agent, a binder, catechol and a solvent. The positive electrode active slurry is made into a secondary battery, and the secondary battery is over-discharged. The area of ​​the diaphragm in the over-discharged secondary battery is divided into n regions. By making the mass ratio of the copper element in the first, second, ... nth regions on the surface of the diaphragm satisfy Formula 1, the conductive agent in the positive electrode active slurry can be distributed more evenly, thereby effectively alleviating the poor wettability of the battery caused by the uneven distribution of the conductive agent, and further improving the problems of rapid resistance growth and severe capacity decay. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a distribution diagram of Cu elements in the diaphragm of the lithium-ion battery after overdischarge in Example 1 of the present invention;

[0042] Figure 2 This is a distribution diagram of Cu elements in the diaphragm of the lithium-ion battery after overdischarge in Example 2 of the present invention;

[0043] Figure 3 This is a distribution diagram of Cu elements in the diaphragm of the lithium ion battery after overdischarge in Comparative Example 1 of the present invention;

[0044] Figure 4 This is a distribution diagram of the Cu element in the diaphragm of the lithium-ion battery in Comparative Example 2 of the present invention after overdischarge. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] As one of the key components of the positive electrode sheet, the conductive agent mainly plays the role of connecting active material particles and transmitting electrons, which has an important impact on the electrical performance of the battery. At present, the commonly used conductive agents mainly include conductive carbon black, conductive graphite, carbon nanotubes, graphene, etc., which have nano-scale sizes and large specific surface areas. Although they can form an efficient conductive network, they are very easy to agglomerate during the slurry preparation process, resulting in poor distribution uniformity of the conductive agent in the positive electrode sheet, affecting the infiltration of the electrolyte, thereby affecting the migration efficiency of lithium ions, causing the battery resistance to increase too fast during the cycle process, and accelerating the capacity decay.

[0047] The inventors have found through research that catechol is a compound with multiple phenolic hydroxyl groups, which can interact with water or other polar solvents without an external catalyst, undergo dehydration polymerization reaction, and form a stable polymer. This polymer can cover the surface of the material, change its chemical and physical properties, and thus enhance the adhesion of the material. Therefore, when catechol is used in the preparation of positive electrode slurry, a layer of polymer film can be covered on the surface of the conductive agent and the active material particles, reducing the specific surface area of ​​the particles, thereby effectively eliminating the agglomeration phenomenon, improving the dispersion effect of the particles, and thus improving the uniformity of the positive electrode active slurry; at the same time, catechol can also interact with the binder, enhance the adhesion of the binder on the positive electrode active material particles, improve the structural stability of the material, and to a certain extent prevent the material from structural collapse during the cycle and resulting in capacity loss.

[0048] The inventors further discovered that the positive electrode active slurry is made into a secondary battery, the negative electrode sheet in the secondary battery includes a negative electrode collector, and the negative electrode collector includes copper; the secondary battery is over-discharged, and the diaphragm of the secondary battery after the over-discharge is divided into n regions. When the mass proportion of the copper element in the first, second, ... nth regions on the surface of the diaphragm satisfies 1-{[(x 1 -x) 2 +(x 2 -x) 2 +……+(x n -x) 2 ] / (n-1)} 1 / 2 When it is ≥90%, the positive electrode active slurry can be guaranteed to have a high uniformity, making the distribution of the conductive agent in the positive electrode sheet more uniform, thereby effectively reducing the resistance growth rate of the battery during the cycle and alleviating capacity attenuation.

[0049] The inventors analyzed that this is mainly because when the secondary battery is overcharged, copper deposition will occur at the negative electrode. The deposited copper ions will diffuse to the positive electrode through the diaphragm. If the conductive agent in the positive electrode is unevenly distributed, more copper ions will be deposited in the negative electrode area corresponding to the conductive agent-rich area in the positive electrode, which will cause more copper elements to remain in the corresponding diaphragm area. Therefore, the distribution of copper elements on the diaphragm can represent to a certain extent whether the conductive agent is evenly distributed in the positive electrode active slurry.

[0050] The present invention divides the separator in the overcharged secondary battery into equal-area regions, performs EDS testing on each region, obtains the mass percentage of copper on the surface of the separator in each region, and calculates the standard deviation of the mass percentage of copper in each region. The standard deviation is the distance that each data deviates from the mean, which can reflect the degree of dispersion of a data set. Therefore, the standard deviation of the mass percentage of copper in each region can determine whether the copper in each region is evenly distributed to a certain extent. Therefore, when 1-{[(x 1 -x) 2 +(x 2 -x) 2 +……+(x n -x) 2 ] / (n-1)} 1 / 2 When it is ≥90%, it indicates that the conductive agent in the positive electrode active slurry is evenly distributed, which can effectively alleviate the poor wettability of the battery caused by uneven distribution of the conductive agent, thereby improving the problems of rapid resistance growth and severe capacity attenuation.

[0051] Based on the above analysis, the first aspect of the present invention provides a positive electrode active slurry, which includes a positive electrode active material, a conductive agent, a binder, catechol and a solvent;

[0052] The positive electrode active slurry is made into a positive electrode sheet, and the positive electrode sheet, the separator, and the negative electrode sheet are stacked in sequence to make a secondary battery; wherein the negative electrode sheet includes a negative electrode collector, and the negative electrode collector includes copper;

[0053] The secondary battery is over-discharged, and the diaphragm area of ​​the over-discharged secondary battery is divided into n regions. The mass ratio of the copper element in the first, second, ... nth regions on the surface of the diaphragm satisfies Formula 1,

[0054] 1-{[(x 1 -x) 2 +(x 2 -x) 2 +……+(x n -x) 2 ] / (n-1)} 1 / 2 ≥90% Formula 1

[0055] In formula 1, x 1 、x 2 ,……x n are the mass percentages of the copper element in the 1st, 2nd, ... nth regions respectively, and x is the average mass percentages of the copper element in the n regions.

[0056] The positive active slurry in the present invention includes a positive active material, a conductive agent, a binder, catechol and a solvent, wherein catechol can interact with water or other polar solvents during the slurry preparation process to undergo a dehydration polymerization reaction to form a stable polymer, which can cover the surface of the conductive agent particles and the positive active material particles, reduce the specific surface area of ​​the particles, and alleviate the agglomeration phenomenon; at the same time, catechol can also interact with the binder to enhance the adhesion between the binder and the particles, and enhance the structural stability of the positive active material. Further, the positive active slurry is made into a secondary battery, and the negative electrode sheet in the secondary battery includes a negative electrode collector, and the negative electrode collector includes copper; the secondary battery is subjected to an over-discharge treatment, and the copper in the negative electrode diffuses to the positive electrode through the diaphragm. When the mass proportion of the copper element in each region of the diaphragm satisfies Formula 1, it means that the conductive agent in the positive active slurry has high dispersibility and uniformity, which can effectively alleviate the problem of poor electrolyte wettability caused by uneven distribution of the conductive agent, thereby effectively reducing the resistance growth rate and relieving capacity decay, and improving the cycle performance of the battery.

[0057] In the present invention, the "mass proportion of the copper element in n regions of the diaphragm" refers to the mass of the copper element in each region as a percentage of the total mass of the solid in the corresponding region, in units of wt%, and can be obtained by testing including the following methods:

[0058] 1) Over-discharging the secondary battery to be tested, specifically, first discharging the secondary battery to be tested at a rate of 10C~1C to 2V, then discharging at a rate of 0.5C~0.1C to 1~0V, leaving it for 1~6h, and then discharging it again at a rate of 0.02C~0.1C to 1~0V; wherein, the third discharge cut-off voltage is not higher than the second discharge cut-off voltage;

[0059] 2) Disassemble the over-discharged secondary battery and remove the diaphragm; clean the diaphragm to remove the particles from the positive electrode or negative electrode remaining on the surface of the diaphragm; then dry the cleaned diaphragm;

[0060] 3) Divide the dried diaphragm into n regions with equal area, perform SEM scanning on each of the n regions to collect energy spectrum data (EDS), and obtain the mass percentage of copper elements in each region.

[0061] Furthermore, in step 2), the over-discharged secondary battery is disassembled in an environment with a dew point of not higher than -40°C. This can prevent the active substances remaining on the diaphragm from chemically reacting in the air, resulting in impurities on the diaphragm surface affecting the test results.

[0062] Furthermore, in step 3), before performing EDS, the surface of the diaphragm to be tested is first purged with compressed air, and then the diaphragm to be tested is placed on the scanning electron microscope sample stage; the placed diaphragm to be tested is dried, and the diaphragm to be tested is fixed on the sample stage with conductive glue; at a certain acceleration voltage, working distance and scanning speed, a SEM image is obtained, and the energy spectrum data of each area is obtained using a point scanning tool, thereby obtaining the mass proportion of the copper element in each area. Among them, the acceleration voltage, working distance and scanning speed can be adjusted according to the characteristics of the diaphragm.

[0063] Furthermore, in step 2), dimethyl carbonate may be used to clean the diaphragm, and the cleaning time is preferably 5 to 30 minutes.

[0064] Furthermore, in step 2), the cleaned diaphragm may be dried at 45° C. for 12 to 24 hours.

[0065] The present invention does not specifically limit the types of the positive electrode active material, the conductive agent and the solvent, which can be selected conventionally in the art.

[0066] For example, the positive electrode active material includes a lithium ion positive electrode active material or a sodium ion positive electrode active material; wherein the lithium ion positive electrode active material includes lithium iron manganese phosphate (LiMn a Fe (1-a) PO 4 , where 0.5≤a≤0.8), lithium iron phosphate (LiFePO 4 ), lithium cobalt oxide (LiCoO 2), lithium manganese oxide (LiMn 2 O 4 ), lithium nickel cobalt manganese oxide (LiNi x Co y Mn (1-x-y) O 2 , where 0.5≤x≤0.96, 0.4≤y≤0.01), lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O 4 )、LiNiO 2 ) and at least one of lithium-rich manganese-based materials; the sodium ion positive electrode active material includes at least one of a transition metal oxide, a Prussian blue / white compound, a polyanion compound, sodium nickel oxide, sodium manganese oxide, sodium iron oxide, sodium ferrous phosphate, and sodium ferric pyrophosphate.

[0067] The conductive agent includes at least one of conductive carbon black, Ketjen black, acetylene black, vapor-grown carbon fiber, graphene, and carbon nanotubes.

[0068] The solvent includes at least one of aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, halogenated hydrocarbon solvents, alcohol solvents, ether solvents, ester solvents, ketone solvents, alcohol ether solvents, sulfone solvents, nitrogen-containing solvents and phenol solvents.

[0069] The binder in the present invention preferably includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, and a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene.

[0070] When the binder includes the aforementioned materials, the fluorine atoms in the binder and the hydroxyl groups in catechol can form hydrogen bonds, which can further enhance the adhesion of the binder on the positive electrode active material, thereby effectively improving the structural stability of the material and enabling the battery to have higher cycle performance.

[0071] When the aforementioned positive electrode active material, conductive agent, binder and solvent are respectively a mixture of the aforementioned multiple specific materials, the present invention does not specifically limit the ratio between the various specific materials.

[0072] The present invention does not specifically limit the sources of the positive electrode active material, the conductive agent, the binder, catechol and the solvent, and commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.

[0073] It can be understood that the positive electrode sheet in the present invention also includes a positive electrode current collector. The present invention does not specifically limit the type of the positive electrode current collector, which can be a conventional choice in the art, for example, aluminum foil can be selected.

[0074] The present invention does not specifically limit the type of the negative electrode current collector, as long as it contains copper; for example, copper foil may be used.

[0075] It can be understood that the negative electrode sheet in the present invention also includes a negative electrode active layer, and the negative electrode active layer also includes a negative electrode active material. The present invention does not specifically limit the type of negative electrode active material. For example, the negative electrode active material includes at least one of Si negative electrode (Si single substance and / or SiO), Sn negative electrode (Sn single substance and / or SnO), and P negative electrode (P single substance).

[0076] The present invention does not specifically limit the type of the diaphragm, which can be selected conventionally in the art. For example, it can be selected from any one of a single-layer polypropylene porous diaphragm, a single-layer polyethylene porous diaphragm, a ceramic-coated polypropylene diaphragm, a ceramic-coated polyethylene diaphragm, a double-layer polypropylene / polyethylene diaphragm, a double-layer polypropylene / polypropylene diaphragm, and a three-layer polypropylene / polyethylene / polypropylene diaphragm.

[0077] Furthermore, the uniformity of the slurry can be further improved by adjusting the mass content of each substance in the positive electrode active slurry and the solid content of the slurry.

[0078] Among them, the mass content of catechol in the positive electrode active slurry will affect the dispersion of the conductive agent and the electrochemical performance of the battery. Too little catechol will cause it to not work, and too much catechol will cause the polymer film formed on the surface of the positive electrode active material to be too thick, affecting the conductivity and electrochemical properties of the material, resulting in poor consistency of electrode resistance, increased internal resistance of the battery, and affected cycle performance and rate performance.

[0079] The mass content of conductive agent in the positive electrode active slurry has a great influence on the overall performance of the battery. Too little conductive agent will result in the inability to form a complete conductive network in the positive electrode sheet, and electrons cannot be transferred in a timely and effective manner, which will increase the polarization internal resistance between the active materials and reduce the high-rate discharge performance. Too much conductive agent will affect the uniformity of the slurry to a certain extent, and will also increase the internal resistance of the battery and increase the risk of thermal runaway.

[0080] The mass content of binder in the positive electrode active slurry also has a great influence on the performance of the battery. Too much binder will reduce the conductivity of the electrode, causing battery performance degradation, and will also increase the risk of thermal runaway; too little binder will easily cause the active material to fall off during the charge and discharge process, affecting the cycle stability of the battery.

[0081] The mass content of the positive electrode active material in the positive electrode active slurry also has a great influence on the electrochemical performance of the battery. Too little content will cause the battery to be unable to fully store and release lithium ions during the charge and discharge process, affecting the battery's energy density and cycle life; too much content will cause the battery to expand in volume during the charge and discharge process, affecting the battery's cycle performance and rate performance.

[0082] Too high a solid content in the positive electrode active slurry will lead to excessive slurry viscosity, affecting the dispersion uniformity of the substances in the slurry system and the battery performance. It will also increase the internal resistance of the battery and affect the energy density and power density of the battery. Too low a solid content will directly affect the peeling strength of the electrode and cause the conductivity of the slurry to decrease, increasing the polarization internal resistance of the battery.

[0083] In a specific embodiment, the mass content of catechol in the positive electrode active slurry is 0.05-1%. Within this range, not only can it be ensured that the positive electrode slurry contains sufficient catechol, but it can also effectively improve the dispersion uniformity of the slurry during the slurry preparation process, and it can also avoid the degradation of electrochemical performance caused by excessive content.

[0084] Illustratively, the mass content of catechol in the positive electrode active slurry is 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8% or 1%.

[0085] In a specific embodiment, the mass content of the conductive agent in the positive electrode active slurry is 1-10%. Within this range, it is not only beneficial to improve the uniformity of the slurry, but also can form a sufficient conductive network to ensure the smooth transmission of electrons and effectively reduce the internal resistance of the battery.

[0086] Illustratively, the mass content of the conductive agent in the positive electrode active slurry is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0087] In a specific embodiment, the mass content of the binder in the positive electrode active slurry is 1-10%. Within this range, not only will the conductivity of the electrode not be affected, but sufficient bonding force can also be provided to the electrode to prevent the active material from falling off during the cycle, thereby effectively improving the cycle performance of the battery.

[0088] Illustratively, the mass content of the binder in the positive electrode active slurry is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0089] In a specific embodiment, the mass content of the positive electrode active material in the positive electrode active slurry is 80-98%. Within this range, not only can the battery have a higher energy density, but also the volume expansion of the battery during the cycle can be effectively alleviated, and the rate performance and cycle performance of the battery can be improved.

[0090] Illustratively, the mass content of the positive electrode active material in the positive electrode active slurry is 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96% or 98%.

[0091] In a specific embodiment, the solid content of the positive electrode active slurry is 48-70%. Within this range, the viscosity of the positive electrode active slurry is moderate, which is conducive to improving the stability of the slurry and increasing the energy density and power density of the battery; at the same time, it can also improve the uniformity of the slurry to a certain extent, reduce the increase in the internal resistance of the battery, and further improve the cycle performance of the battery.

[0092] Illustratively, the solids content is 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68% or 70%.

[0093] The second aspect of the present invention provides a quality control method for positive electrode active slurry, wherein the positive electrode active slurry of the first aspect is made into a positive electrode sheet, and the positive electrode sheet, the separator, and the negative electrode sheet are stacked in sequence to make a secondary battery; wherein the negative electrode sheet includes a negative electrode current collector, and the negative electrode current collector includes copper;

[0094] The secondary battery is over-discharged, and the diaphragm area of ​​the over-discharged secondary battery is divided into n regions. The mass ratio of the copper element in the first, second, ... nth regions on the surface of the diaphragm satisfies Formula 1,

[0095] 1-{[(x 1 -x) 2 +(x 2 -x) 2 +……+(x n -x) 2 ] / (n-1)} 1 / 2 ≥90% Formula 1

[0096] In formula 1, x 1 、x 2 ,……x n are the mass percentages of the copper element in the 1st, 2nd, ... nth regions respectively, and x is the average mass percentages of the copper element in the n regions.

[0097] The above-mentioned quality control method can be used to efficiently detect the uniformity of the distribution of the conductive agent in the positive electrode active slurry. Specifically, the positive electrode active slurry is made into a positive electrode sheet, and the positive electrode sheet, the diaphragm, and the negative electrode sheet are stacked and assembled into a secondary battery in sequence, wherein the current collector in the negative electrode sheet includes copper. The secondary battery is over-discharged, which causes the oxidation and dissolution of the negative electrode copper, and the copper precipitation phenomenon occurs. The precipitated copper ions diffuse to the positive electrode through the diaphragm. If the conductive agent in the positive electrode is unevenly distributed, there will be conductive agent-enriched areas and poor areas in the positive electrode. The negative electrode area corresponding to the enriched area has more copper ions precipitated, and the negative electrode area corresponding to the poor area has less copper ions precipitated. The diaphragm is located between the positive and negative electrodes. When the copper ions pass through the diaphragm, some of them will remain in the diaphragm. Therefore, the distribution of the residual copper element on the diaphragm can represent whether the conductive agent in the slurry is evenly distributed to a certain extent. By performing EDS tests on various areas of the diaphragm, the mass proportion of copper elements in each area is obtained, and the standard deviation of the mass proportion of copper elements in each area is calculated (i.e., Formula 1). When Formula 1 is satisfied, it means that the conductive agent in the positive electrode active slurry is evenly distributed, thereby achieving accurate judgment of the slurry uniformity.

[0098] The third aspect of the present invention provides a method for preparing the positive electrode active slurry of the first aspect, comprising the following steps:

[0099] The positive electrode active material, the conductive agent and the catechol are premixed, during which the revolution speed is 10-40 rpm, the dispersion speed is 300-600 rpm, and the mixing time is 30-60 min to obtain a dry material;

[0100] Mixing the binder with the solvent to obtain a binder glue solution, and dividing the binder glue solution into a first binder glue solution and a second binder glue solution;

[0101] The first binder glue and the dry material are first mixed to obtain a first slurry; during the first mixing, the revolution speed is 20-50 rpm, the dispersion speed is 1000-4000 rpm, the vacuum degree is -40 KPa-85 KPa, and the mixing time is 60-120 min;

[0102] The second binder glue is mixed with the first slurry for a second time to obtain a second slurry; in the second mixing, the revolution speed is 20-50 rpm, the dispersion speed is 1000-4000 rpm, the vacuum degree is -40--100 KPa, and the mixing time is 60-120 min;

[0103] The second slurry is subjected to ultrasonic treatment to obtain a third slurry; the third slurry is mixed with a solvent for a third time to obtain a positive electrode active slurry.

[0104] Specifically, the positive electrode active material, the conductive agent and catechol are first premixed, and during this process, the revolution speed is maintained at 10-40 rpm, the dispersion speed is maintained at 300-600 rpm, and the mixing time is maintained at 30-60 minutes to obtain a dry material.

[0105] Secondly, the binder and the solvent are uniformly mixed to obtain a binder glue solution, and the obtained binder glue solution is divided into two parts, namely a first binder glue solution and a second binder glue solution.

[0106] Next, the first binder glue and the dry material are mixed for the first time. During this process, the revolution speed is maintained at 20-50 rpm, the dispersion speed is maintained at 1000-4000 rpm, the vacuum degree is maintained at -40 KPa-85 KPa, and the mixing time is maintained at 60-120 min to obtain a first slurry.

[0107] Next, the second binder glue is mixed with the first slurry for a second time, during which the revolution speed is maintained at 20-50 rpm, the dispersion speed is maintained at 1000-4000 rpm, the vacuum degree is maintained at -40--100 KPa, and the mixing time is maintained at 60-120 min to obtain a second slurry.

[0108] Finally, the second slurry is subjected to ultrasonic treatment to obtain a third slurry; the third slurry is mixed with a solvent for a third time to obtain a positive electrode active slurry.

[0109] Illustratively, during premixing, the revolution speed is 10rpm, 15rpm, 20rpm, 25rpm, 30rpm, 35rpm or 40rpm; the dispersion speed is 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm or 600rpm; and the mixing time is 30min, 35min, 40min, 45min, 50min, 55min, 60min.

[0110] Illustratively, in the first mixing, the revolution speed is 20rpm, 25rpm, 30rpm, 35rpm, 40rpm, 45rpm or 50rpm; the dispersion speed is 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm or 4000rpm; the vacuum degree is -40KPa, -45KPa, -50KPa, -55KPa, -60KPa, -65KPa, -70KPa, -75KPa, -80KPa or -85KPa; the mixing time is 60min, 70min, 80min, 90min, 100min, 110min or 120min.

[0111] Illustratively, in the second mixing, the revolution speed is 20rpm, 25rpm, 30rpm, 35rpm, 40rpm, 45rpm or 50rpm; the dispersion speed is 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm or 4000rpm; the vacuum degree is -40KPa, -50KPa, -60KPa, -70KPa, -80KPa, -90KPa or -100KPa; and the mixing time is 60min, 70min, 80min, 90min, 100min, 110min or 120min.

[0112] It should be noted that the positive electrode active material, conductive agent, catechol and binder can be dried before pre-mixing to remove moisture and volatile impurities in the materials, which not only helps to reduce chemical reactions and physical agglomeration in the subsequent mixing process, but also helps catechol to contact the surface of the positive electrode active material and conductive agent, thereby improving the dispersion effect.

[0113] The present invention does not specifically limit the method and conditions of the drying treatment. For example, the drying treatment can be carried out by vacuum drying, with a drying temperature of 105-150° C. and a drying time of 24-60 hours.

[0114] The method for preparing the positive electrode active slurry of the present invention reduces the agglomeration and aggregation between particles and improves the dispersibility of the conductive agent between materials, thereby laying a foundation for the subsequent slurrying process by premixing the positive electrode material, the conductive agent and catechol.

[0115] Subsequently, the prepared binder glue is divided into two parts, namely the first binder glue and the second binder glue. The first binder glue and the second binder glue are mixed with the dry material in batches under specific conditions. A vacuum is maintained during the mixing process, which helps to remove the gas adsorbed on the surface of catechol, expose the surface of catechol, reduce the bonding force between molecules, and make the chemical bonds on its surface easier to break and undergo dehydration polymerization reaction, forming a stable polymer film on the surface of the conductive agent and the positive active material, reducing agglomeration and improving the dispersion effect. In addition, the specific revolution speed, dispersion speed and mixing time in the first mixing and the second mixing also help to further improve the uniformity of the slurry. In addition, the batch addition of the binder glue helps to reduce the possibility of bubble generation and entrained gas during the mixing process, effectively improving the stability of the mixed slurry.

[0116] Next, the second slurry is treated with ultrasound to improve the mixing uniformity of the components in the slurry, promote better contact between the reactants, and accelerate the rate of chemical reactions under the energy of ultrasound. Ultrasonic waves can also form tiny cavities in the slurry (called cavitation), generating local high temperatures and high pressures, further promoting the film-forming effect of catechol and improving the uniformity of the slurry.

[0117] Finally, the third slurry after ultrasonic treatment is mixed with a solvent to obtain the final positive electrode active slurry. During the entire mixing process, the solid content of the slurry is gradually reduced. This method puts each component in the slurry in a suitable internal friction range, further improving the dispersion effect of the positive electrode active slurry.

[0118] The above preparation method can make the conductive agent in the prepared positive electrode active slurry have higher dispersibility and uniformity, so that the electrochemical performance of the positive electrode sheet is better, the resistance growth of the battery is effectively reduced, and the cycle stability of the battery is improved.

[0119] Furthermore, the solid content of the binder paste, the amount of the first binder paste or the amount of the second binder paste may be adjusted to further improve the uniformity of the positive electrode active slurry.

[0120] Among them, the solid content of the binder glue will affect the dispersion effect of catechol. If the solid content of the binder glue is too high, it may cause particle agglomeration or sedimentation, affecting the uniformity and stability of the glue; if the solid content is too low, it is easy to cause excessive catechol, which in turn causes too much catechol to bind to the surface of the positive electrode active material particles, affecting the electrochemical performance of the battery.

[0121] The percentage of the first binder or the second binder in the total binder colloid weight will have a significant impact on the dispersion of the positive electrode active material particles. A suitable percentage can effectively prevent the particles from settling and agglomerating, and improve the stability of the slurry. However, if the first binder or the second binder accounts for too large a percentage, the positive electrode active material may be over-wrapped, forming a strong adhesion force, resulting in poor fluidity between particles, thereby affecting the fluidity and dispersibility of the slurry.

[0122] In a specific embodiment, the solid content of the binder glue is 3-15%. Within this range, the viscosity of the binder glue is moderate, which can effectively reduce the friction between particles, enable catechol to more easily penetrate and cover each particle, and improve the dispersion effect of the slurry.

[0123] Exemplarily, the solid content of the binder glue is 3%, 5%, 7%, 9%, 11% or 13%, 15%.

[0124] In a specific embodiment, the weight of the first binder glue accounts for 40-60% of the weight of the binder glue. Within this range, not only can the slurry sedimentation be effectively prevented and the stability of the slurry be improved, but also the positive electrode active material can be prevented from being excessively wrapped, which affects the fluidity and dispersibility of the slurry.

[0125] Illustratively, the weight of the first binder glue accounts for 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58% or 60% of the weight of the binder glue.

[0126] In a specific embodiment, the weight of the second binder glue accounts for 40-60% of the weight of the binder glue. Within this range, it helps to improve the overall stability and dispersibility of the slurry.

[0127] Illustratively, the weight of the second binder glue accounts for 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58% or 60% of the weight of the binder glue.

[0128] Furthermore, the conditions of the ultrasonic treatment, such as the ultrasonic time and the vibration frequency, can be controlled to further improve the dispersion effect of the slurry.

[0129] In a specific embodiment, during the ultrasonic treatment, the ultrasonic time is 10 to 60 minutes and the vibration frequency is 20 to 100 kHz. Within this range, it is helpful for the reactants to fully react, further improve the film-forming effect of catechol, and further improve the uniformity of the positive active slurry.

[0130] Exemplarily, the ultrasound time is 10 min, 20 min, 30 min, 40 min, 50 min or 60 min; the vibration frequency is 20 kHz, 30 kHz, 40 kHz, 50 kHz, 60 kHz, 70 kHz, 80 kHz, 90 kHz or 100 kHz.

[0131] Furthermore, the mixing conditions in the third mixing may be controlled to improve the overall uniformity of the final positive electrode active slurry.

[0132] In a specific embodiment, in the third mixing, the revolution speed is 20-50 rpm, the dispersion speed is 1000-4000 rpm, the vacuum degree is -40--100 KPa, and the mixing time is 40-120 min. Within this range, it is helpful to evenly mix the third slurry with the solvent and improve the uniformity of dispersion of each component in the slurry.

[0133] Exemplarily, the revolution speed is 20rpm, 25rpm, 30rpm, 35rpm, 40rpm or 50rpm; the dispersion speed is 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm or 4000rpm; the vacuum degree is -40KPa, -50KPa, -60KPa, -70KPa, -80KPa, -90KPa or -100KPa; and the mixing time is 40min, 60min, 80min, 100min or 120min.

[0134] A fourth aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector;

[0135] The positive electrode active layer is prepared from the positive electrode active slurry of the first aspect or the positive electrode active slurry prepared by the preparation method of the second aspect.

[0136] The conductive agent in the positive electrode sheet is evenly distributed, which can effectively improve the electrolyte wettability problem caused by uneven distribution of the conductive agent, thereby effectively reducing the battery resistance growth rate and improving the battery capacity retention rate.

[0137] The fifth aspect of the present invention provides a secondary battery, which comprises the positive electrode sheet of the third aspect, so that the secondary battery has a lower resistance growth rate and a higher cycle capacity retention rate.

[0138] A sixth aspect of the present invention provides an electronic device, which includes the secondary battery according to the fifth aspect, so that the electronic device has a longer service life.

[0139] Hereinafter, the secondary battery prepared by the positive electrode active slurry of the present invention will be described in detail through specific examples.

[0140] Example 1

[0141] 1) Preparation of positive electrode active slurry

[0142] The positive electrode active material LiNi 0.83 Co 0.1 Mn 0.07 O 2 , conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are placed in a vacuum drying oven at 120°C for 48 hours for drying and standby use;

[0143] The dried PVDF and solvent N-methylpyrrolidone (NMP) are uniformly mixed to obtain a binder solution with a solid content of 10%; the binder solution is divided into two parts, namely a first binder solution (accounting for 60% of the binder solution) and a second binder solution (accounting for 40% of the binder solution);

[0144] The dried positive electrode active material, conductive agent and catechol are pre-mixed by double planetary stirring, during which the revolution speed is 20 rpm, the dispersion speed is 600 rpm, and the mixing time is 40 min to obtain a dry material;

[0145] The first binder glue solution is mixed with the dry material. During the mixing process, the revolution speed is 40 rpm, the dispersion speed is 1500 rpm, the vacuum degree is -80 KPa, and the mixing time is 60 min to obtain a first slurry;

[0146] The first slurry was mixed with the second binder glue. During the mixing process, the revolution speed was 40 rpm, the dispersion speed was 2000 rpm, the vacuum degree was -70 KPa, and the stirring time was 90 min to obtain the second slurry;

[0147] The second slurry was subjected to ultrasonic treatment, the ultrasonic time was 60 min, and the vibration frequency was 80 kHz, to obtain a third slurry;

[0148] The third slurry was mixed with the solvent. During the mixing process, the revolution speed was 40 rpm, the dispersion speed was 3000 rpm, the vacuum degree was -80 KPa, and the mixing time was 90 min. The positive electrode active slurry of this embodiment was obtained, wherein the positive electrode active material LiNi 0.83 Co 0.1 Mn 0.07 O 2 The mass ratio of conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and catechol is 96:2:1.8:0.2, and the solid content is 60%.

[0149] 2) Preparation of positive electrode

[0150] The positive electrode active slurry is coated on both surfaces of the aluminum foil, and the positive electrode sheet of this embodiment is obtained after drying, rolling and slitting.

[0151] 3) Negative electrode preparation

[0152] The negative electrode active material graphite, the dispersant carboxymethyl cellulose (CMC), the conductive agent SP and the binder styrene butadiene rubber (SBR) were added into a stirring tank in a mass ratio of 95.5:1.5:1:2, and deionized water was added. After sufficient stirring, the negative electrode active slurry was prepared. The negative electrode slurry was coated on both surfaces of the copper foil by a coating machine, and the negative electrode sheet of this embodiment was obtained after drying (100°C), rolling and slitting.

[0153] 4) Electrolyte

[0154] The electrolyte consists of lithium hexafluorophosphate (LiPF 6), ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and fluoroethylene carbonate (FEC), among which LiPF 6 The content in the electrolyte is 1M, the volume ratio of EC, EMC and DEC is 1:1:1, and the mass percentage of FEC in the electrolyte is 2%.

[0155] 5) Diaphragm

[0156] Adopt polypropylene PP diaphragm.

[0157] 6) Lithium-ion battery preparation

[0158] The positive electrode sheet, separator and negative electrode sheet are stacked in sequence, wound to form a battery cell, and then packaged with aluminum plastic film, baked to remove moisture, and then injected with electrolyte. After subsequent treatments such as formation and secondary sealing, the lithium-ion battery of this embodiment is obtained.

[0159] Example 2

[0160] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that the mass ratio of the positive electrode active material, the conductive agent, the binder and the catechol is 95.8:2:1.8:0.4.

[0161] Example 3

[0162] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that the mass ratio of the positive electrode active material, the conductive agent, the binder and the catechol is 96.15:2:1.8:0.05, and the solid content is 48%;

[0163] The premixing revolution speed was 10 rpm, the dispersion speed was 300 rpm, and the mixing time was 30 min;

[0164] In the first mixing, the revolution speed is 20 rpm, the dispersion speed is 1000 rpm, the vacuum degree is -40 KPa, and the mixing time is 60 min to obtain a first slurry;

[0165] In the second mixing, the revolution speed is 20 rpm, the dispersion speed is 1000 rpm, the vacuum degree is -40 KPa, and the stirring time is 60 min to obtain a second slurry;

[0166] The ultrasonic time was 10 min and the vibration frequency was 20 kHz; in the third mixing process, the revolution speed was 20 rpm, the dispersion speed was 1000 rpm, the vacuum degree was -40 KPa, and the mixing time was 40 min;

[0167] The solid content of the adhesive solution is 3%, the first adhesive accounts for 40% of the adhesive solution, and the second adhesive accounts for 60% of the adhesive solution.

[0168] Example 4

[0169] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that the mass ratio of the positive electrode active material, the conductive agent, the binder and the catechol is 95.2:2:1.8:1, and the solid content is 70%;

[0170] The premixing revolution speed was 40 rpm, the dispersion speed was 600 rpm, and the mixing time was 60 min;

[0171] In the first mixing process, the revolution speed is 50 rpm, the dispersion speed is 4000 rpm, the vacuum degree is -85 KPa, and the mixing time is 120 min to obtain a first slurry;

[0172] In the second mixing process, the revolution speed is 50 rpm, the dispersion speed is 4000 rpm, the vacuum degree is -100 KPa, and the stirring time is 120 min to obtain a second slurry;

[0173] The ultrasonic time was 60 min, the vibration frequency was 100 kHz, the revolution speed in the third mixing process was changed to 50 rpm, the dispersion speed was 4000 rpm, the vacuum degree was -100 KPa, and the mixing time was 120 min;

[0174] The solid content of the adhesive solution is 15%, the first adhesive accounts for 50% of the adhesive solution, and the second adhesive accounts for 50% of the adhesive solution.

[0175] Example 5

[0176] The preparation method of the battery in this embodiment is basically the same as that in Embodiment 1, except that the battery system is changed to a sodium ion battery system, specifically:

[0177] Replace the positive electrode active material with Na 2 / 3 [Ni 1 / 3 Mn 2 / 3 ]O 2 ;

[0178] Adjust the preparation of the negative electrode sheet: add the negative electrode active material hard carbon, the conductive agent SP and the binder PVDF into a stirring tank in a mass ratio of 94:2:4, add the solvent NMP, and prepare a negative electrode active slurry with a solid content of 50% after sufficient stirring; use a coating machine to coat the negative electrode active slurry on both surfaces of the current collector copper foil, and obtain the negative electrode sheet of this embodiment after drying (100°C), rolling and slitting.

[0179] Example 6

[0180] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass ratio of the positive electrode active material, the conductive agent, the binder and the catechol is 96.19:2:1.8:0.01.

[0181] Example 7

[0182] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), the mass ratio of the positive electrode active material, the conductive agent, the binder and the catechol is 95.5.15:2:1.8:1.5

[0183] Example 8

[0184] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the solid content of the positive electrode active slurry is 72%.

[0185] Example 9

[0186] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the weight of the first binder glue accounts for 37% of the weight of the binder glue, and the weight of the second binder glue accounts for 63% of the weight of the binder glue.

[0187] Example 10

[0188] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the solid content of the binder glue is 2%.

[0189] Comparative Example 1

[0190] The preparation method of the lithium-ion battery in this comparative example is basically the same as that in Example 1, except that the positive electrode active slurry does not contain catechol, and accordingly, the mass ratio of the positive electrode active material, the conductive agent and the binder is 96:2:2.

[0191] Comparative Example 2

[0192] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that the preparation of the positive electrode active slurry is different, specifically:

[0193] The positive electrode active material LiNi 0.83 Co 0.1 Mn 0.07 O 2 , conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are placed in a vacuum drying oven at 120°C for 48 hours for drying and standby use;

[0194] The dried PVDF was mixed evenly with the solvent N-methylpyrrolidone (NMP) to obtain a binder glue solution with a solid content of 10%;

[0195] The dried positive electrode active material, conductive agent and catechol are pre-mixed by double planetary stirring, during which the revolution speed is 20 rpm, the dispersion speed is 600 rpm, and the mixing time is 40 min to obtain a dry material;

[0196] The binder glue was mixed with the dry material. During the mixing process, the revolution speed was 40rpm, the dispersion speed was 1000rpm, the vacuum degree was -85KPa, and the mixing time was 90min. Then, the solvent was added to the mixed slurry for mixing. During the mixing process, the revolution speed was 40rpm, the dispersion speed was 3000rpm, the vacuum degree was -80KPa, and the mixing time was 90min. A positive electrode active slurry with a solid content of 60% was obtained, in which the positive electrode active material LiNi 0.83 Co 0.1 Mn 0.07 O 2 The mass ratio of conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and catechol is 96:2:1.8:0.2.

[0197] Comparative Example 3

[0198] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), during the premixing process, the premixing revolution speed is changed to 5 rpm, the dispersion speed is 100 rpm, and the mixing time is 20 min.

[0199] Comparative Example 4

[0200] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the revolution speed in the first mixing process is changed to 10 rpm and the dispersion speed is changed to 500 rpm to obtain the first slurry.

[0201] Comparative Example 5

[0202] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the first slurry is not prepared under vacuum conditions but is prepared at normal temperature and pressure.

[0203] Comparative Example 6

[0204] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the revolution speed in the second mixing process is changed to 10 rpm and the dispersion speed is changed to 500 rpm to obtain the second slurry.

[0205] Test example

[0206] 1. The uniformity of the positive electrode active slurry in the above-mentioned embodiment and comparative example is tested, which specifically includes the following steps:

[0207] The secondary battery was discharged at a rate of 1C to 2V, then discharged at a rate of 0.5C to 1V, and after standing for 1h, discharged again at a rate of 0.1C to 0.2V;

[0208] Disassemble the over-discharged battery in a dew point room below -40°C, remove the diaphragm in the center area of ​​the pole piece (i.e., the diaphragm excluding the head and tail as well as the upper and lower edge areas); clean the diaphragm with dimethyl carbonate for 10 minutes, and dry the cleaned diaphragm at 45°C for 12 hours;

[0209] The dried diaphragm is divided into 9 areas, and each area is scanned by SEM to collect energy spectrum data (EDS). The mass percentage of copper elements in the 9 areas is obtained by the point scanning tool. The mass percentage of copper elements in each area is substituted into Formula 1 to obtain the calculation results, as shown in Tables 1 and 2.

[0210] Figure 1 is a distribution diagram of Cu element in the diaphragm of the lithium ion battery after overdischarge in Example 1, Figure 2 is the distribution diagram of Cu element in the diaphragm of the lithium ion battery after overdischarge in Example 2, Figure 3 is the Cu element distribution diagram in the diaphragm of the lithium ion battery in comparative example 1 after overdischarge, Figure 4 This is the distribution diagram of Cu element in the diaphragm of the lithium-ion battery in Comparative Example 2 after overdischarge.

[0211] Depend on Figure 1-Figure 4 It can be seen that compared with Comparative Examples 1 and 2, the Cu element distribution in the separators in Examples 1 and 2 is more uniform, indicating that the positive electrode active slurries prepared in Examples 1 and 2 are more uniform. This shows that the positive electrode active slurry in the present invention has excellent uniformity and can effectively solve the problem of uneven distribution of the conductive agent.

[0212] 2. The resistance growth rate and cycle performance of the secondary batteries in the above embodiments and comparative examples were tested. The test results are shown in Table 1.

[0213] 1) Resistance growth rate

[0214] The battery was charged to 4.25V at 1C constant current, then charged to 0.05C at constant voltage, and left for 30 minutes. At this time, the battery was fully charged. The voltage V at the end of the rest period was recorded. 0 ; Then discharge at 1C (current is recorded as I) for 10s, and record the voltage V at the end of discharge 1 , then the DC resistance (DCR) growth rate (%) = (V1 -V 0 ) / I×100%.

[0215] 2) Cycle capacity retention rate

[0216] At 25°C, charge the battery to 4.25V at 1C, and then discharge it to 2.8V at 1C. Record the initial discharge capacity as C. 0 ; Cycle according to the above charge and discharge mechanism, and record the discharge capacity when the cycle reaches 500 cycles as C 1 , then the battery capacity retention rate (%) = C 1 / C 0 ×100%.

[0217] Table 1

[0218]

[0219] Table 2

[0220]

[0221] From Table 1 and Table 2, we can see that:

[0222] Compared with Comparative Examples 1-6, the variance of the mass proportion of copper elements in Examples 1-10 is smaller, which indicates that the positive electrode active slurry has good dispersion uniformity, and accordingly, the battery's cycle capacity decay and DCR growth are slower. Specifically, the cycle capacity retention rate in Example 1 can reach up to 95.7%, and the cycle DCR growth rate can reach as low as 8.3%, and the battery performance is significantly higher than that of the comparative example. It can be seen that the conductive agent of the positive electrode active slurry in the present invention is evenly distributed, which can effectively reduce the resistance growth of the battery and improve the cycle stability of the battery. At the same time, it also shows that the evaluation results of the positive electrode active slurry quality control method in the present invention are relatively accurate, and accurate judgment of the slurry uniformity can be achieved.

[0223] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode active slurry, characterized in that: The positive electrode active slurry comprises a positive electrode active material, a conductive agent, a binder, catechol and a solvent; The positive electrode active slurry is made into a positive electrode sheet, and the positive electrode sheet, a separator, and a negative electrode sheet are stacked in sequence to make a secondary battery; wherein the negative electrode sheet includes a negative electrode current collector, and the negative electrode current collector includes copper; The secondary battery is over-discharged, and the area of ​​the separator in the over-discharged secondary battery is divided into n regions, and the mass proportion of the copper element in the first, second, ... nth regions on the surface of the separator satisfies Formula 1, 1 - {[(x1 - x) 2 + (x2 - x) 2 + …… + (x n - x) 2 / (n - 1)} 1 / 2 ≥ 90% Formula 1 In formula 1, x1, x2, ... x n are the mass percentages of the copper element in the 1st, 2nd, ... nth regions respectively, and x is the average mass percentages of the copper element in the n regions.

2. The positive electrode active slurry according to claim 1, characterized in that: The mass content of catechol in the positive electrode active slurry is 0.05-1%; And / or, the mass content of the conductive agent in the positive electrode active slurry is 1-10%; And / or, the mass content of the binder in the positive electrode active slurry is 1-10%; And / or, the mass content of the positive electrode active material in the positive electrode active slurry is 80-98%.

3. The positive electrode active slurry according to claim 1 or 2, characterized in that: The solid content of the positive electrode active slurry is 48-70%.

4. A quality control method for positive electrode active slurry, characterized in that: The positive electrode active slurry according to any one of claims 1 to 3 is made into a positive electrode sheet, and the positive electrode sheet, the separator, and the negative electrode sheet are stacked in sequence to make a secondary battery; wherein the negative electrode sheet comprises a negative electrode current collector, and the negative electrode current collector comprises copper; The secondary battery is over-discharged, and the area of ​​the separator in the over-discharged secondary battery is divided into n regions, and the mass proportion of the copper element in the first, second, ... nth regions on the surface of the separator satisfies Formula 1, 1 - {[(x1 - x) 2 +(x2 - x) 2 +……+(x n - x) 2 / (n - 1)} 1 / 2 ≥90% Formula 1 In formula 1, x1, x2, ... x n are the mass percentages of the copper element in the 1st, 2nd, ... nth regions respectively, and x is the average mass percentages of the copper element in the n regions.

5. A method for preparing the positive electrode active slurry according to any one of claims 1 to 3, characterized in that: The following steps are involved: Premixing the positive electrode active material, the conductive agent and catechol, wherein the revolution speed is 10-40 rpm, the dispersion speed is 300-600 rpm and the mixing time is 30-60 min to obtain a dry material; Mixing the binder with the solvent to obtain a binder glue solution, and dividing the binder glue solution into a first binder glue solution and a second binder glue solution; The first binder glue and the dry material are first mixed to obtain a first slurry; in the first mixing, the revolution speed is 20-50 rpm, the dispersion speed is 1000-4000 rpm, the vacuum degree is -40 KPa-85 KPa, and the mixing time is 60-120 min; The second binder glue is mixed with the first slurry for a second time to obtain a second slurry; in the second mixing, the revolution speed is 20-50 rpm, the dispersion speed is 1000-4000 rpm, the vacuum degree is -40--100 KPa, and the mixing time is 60-120 min; The second slurry is subjected to ultrasonic treatment to obtain a third slurry; the third slurry is subjected to a third mixing with a solvent to obtain the positive electrode active slurry.

6. The method for preparing the positive electrode active slurry according to claim 5, characterized in that: The solid content of the adhesive glue is 3-15%; and / or, the weight of the first adhesive glue accounts for 40-60% of the weight of the adhesive glue; And / or, the weight of the second adhesive solution accounts for 40-60% of the weight of the adhesive solution.

7. The method for preparing the positive electrode active slurry according to claim 5 or 6, characterized in that: In the ultrasonic treatment, the ultrasonic time is 10 to 60 minutes and the vibration frequency is 20 to 100 kHz; And / or, in the third mixing, the revolution speed is 20-50 rpm, the dispersion speed is 1000-4000 rpm, the vacuum degree is -40--100 KPa, and the mixing time is 40-120 min.

8. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector; The positive electrode active layer is prepared from the positive electrode active slurry described in any one of claims 1 to 3, or the positive electrode active slurry prepared by the preparation method described in any one of claims 5 to 7.

9. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet according to claim 8.

10. An electronic device, characterized in that: The electronic device comprises the secondary battery according to claim 9.

Citation Information

Cited By

  • All-solid-state positive pole piece as well as preparation method and application thereof

    CN120497279A